Concepções epistemológicas e pedagógicas da ação docente de professores de Ciências - Fersula, Michele Gonçalves (2013)
The speeches, arguments and justifications used by teachers in their everyday practice may reveal the theoretical perception in which they are immersed. Such perceptions are not created at random, otherwise they come from the assumption that it is natural to be and thinks this way. They emerge as a possibility to carry out their job and as a reflex of what they have lived, which, in turn, fundaments the conceptions that surround them. The teachers adhere to a set of values and principles that are considered to be relevant to promote learning. They assume some behaviour influenced by both the professional environment and personal reasons. Professional and personal reasons incorporated to the pedagogical practice comprise the epistemology of teaching practice, which are translated in a pedagogical model that reveals the conceptions of the teachers regarding teaching and learning. Based on it, we investigated the epistemology of science teachers working for the city hall in Pelotas (RS Brazil) and how this affects their teaching practice. Qualitative research concepts were used along with two key concepts: epistemological issues and teacher s practice. The results showed there is a diversity of epistemological principles along with the pedagogical conceptions of the teachers and for them it is natural to mix a constructivist approach with a model of behaviourist teaching. In such practices the teachers mobilize different rituals that are not always transformed into effective learning. We should call the attention to the fact that the act of thinking about their own teaching practice is a limited or inexistent one, and we believe that such act can be achieved by metanalysis, being the reflexive process and the development of autonomy the key elements. If they do so, the teachers may review the bases on which their pedagogical conceptions are built and then be able to think about their identity process and professional practice on a more critical base